2009
DOI: 10.1007/s00702-009-0232-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha lipoic acid on the tardive dyskinesia and oxidative stress induced by haloperidol in rats

Abstract: Haloperidol (HAL) is a widely used neuroleptic drug for the treatment of acute and chronic psychosis. Tardive dyskinesia (TD) is a complex hyperkinetic syndrome consisting of choreiform and athetoid movements, which persists for months or years after withdrawal. Increased levels of thiobarbituric acid reactive products are found in the cerebrospinal fluid and plasma of patients treated with neuroleptics, especially those with movement disorders. Alpha lipoic acid (ALA), a natural metabolic antioxidant, is effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…Therefore, ALA supplementation is thought to possess anti depressant activity. In the present study also it was found that ALA significantly increased the locomotor activity which was considerably reduced by phenytoin [43].…”
Section: Effect Of Alpha Lipoic Acid On Phenytoin Induced Behaviouralsupporting
confidence: 78%
“…Therefore, ALA supplementation is thought to possess anti depressant activity. In the present study also it was found that ALA significantly increased the locomotor activity which was considerably reduced by phenytoin [43].…”
Section: Effect Of Alpha Lipoic Acid On Phenytoin Induced Behaviouralsupporting
confidence: 78%
“…Other reports also implicate OS related genes to TD [178][179][180]. AOs vitamin E [181], resveratrol [182], alpha lipoic acid [183], and quercetin [184] administration is beneficial to patients.…”
Section: Tardive Dyskinesia (Td)mentioning
confidence: 99%
“…Thus, it is widely used to induce acute toxic hepatic damage through oxidative stress, membrane damage and accumulation of lipid droplets in the hepatocyte cytoplasm (Koen et al, 2013). Alpha lipoic acid (ALA), also named as thiotic acid, is a natural cofactor that is synthesized inside the plant and animal mitochondria (Thaakur and Himabindhu, 2009). ALA has recently used as a protective agent for many pathological alterations that are due to oxidative stress (Li et al, 2012 andWang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%